DNA binding modes influence Rap1 activity in the regulation of telomere length and MRX functions at DNA ends. Issue 5 (27th December 2019) - Bonetti, Diego; Rinaldi, Carlo; Vertemara, Jacopo; Notaro, Marco; Pizzul, Paolo; Tisi, Renata; Zampella, Giuseppe; Longhese, Maria Pia
Abstract: The cellular response to DNA double-strand breaks (DSBs) is initiated by the Mre11–Rad50–Xrs2 (MRX) complex that has structural and catalytic functions. MRX association at DSBs is counteracted by Rif2, which is known to interact with Rap1 that binds telomeric DNA through two tandem Myb-like domains. Whether and how Rap1 acts at DSBs is unknown. Here we show that Rif2 inhibits MRX association to DSBs in a manner dependent on Rap1, which binds to DSBs and promotes Rif2 association to them. Rap1 in turn can negatively regulate MRX function at DNA ends also independently of Rif2. In fact, a characterization of Rap1 mutant variants shows that Rap1 binding to DNA through both Myb-like domains results in formation of Rap1-DNA complexes that control MRX functions at both DSBs and telomeres primarily through Rif2. By contrast, Rap1 binding to DNA through a single Myb-like domain results in formation of high stoichiometry complexes that act at DNA ends mostly in a Rif2-independent manner. Altogether these findings indicate that the DNA binding modes of Rap1 influence its functional properties, thus highlighting the structural plasticity of this protein.